FUS, PDSS2, SMAD4, CUL2 e HSPA9 no tecido prostático: como possíveis marcadores de agressividade tumoral e resposta à terapia adjuvante e de resgate após prostatectomia - Hirth, Carlos Gustavo (2021)
Prostatic adenocarcinoma is the second-most prevalent type of neoplasia in men, with a considerable divergence between the number of new cases and mortality. Thus, risk stratification is important when planning therapy. A range of markers have been proposed to predict disease development. Recent proteomic studies suggest proteins like FUS, PDSS2, DERL1, YBX1, pS6, SMAD4, CUL2 and HSPA9 may be useful in stratification, but little information is available on these markers and results have been inconsistent. In this study, we compared the expression of these markers by submitting prostatic tissue to immunohistochemical analysis, and tested for associations between Gleason patterns 3 and 4 and ISUP grade, as well as associations between aggressiveness and postoperative/post-therapy clinical and laboratory progress of patients submitted to prostatectomy. Using tissue microarrays in combination with immunohistochemistry, we determined the protein expression of samples of neoplastic and non-neoplastic tissue from a retrospective cohort of 636 prostatectomized patients. Adenocarcinoma was segregated into Gleason patterns 3, 4 and 5. We then calculated the odds ratio of low-grade samples being associated with intermediate or high-grade neoplasia when positive for the tested markers, and calculated the odds ratio of Gleason pattern 4 remaining as intermediate or high-grade neoplasia. We also studied the association between the immunoexpression of the markers in neoplastic tissue and progress of serum PSA levels after surgery, adjuvant therapy and salvage therapy period and progression to systemic disease. In the univariate analysis, positivity for FUS, SMAD4 and HSPA9 in Gleason pattern 3 adenocarcinoma was associated with higher risk of ISUP grade >1 neoplasia, with significance maintained for FUS and HSPA9 in the multivariate analysis. Gleason pattern 4 adenocarcinoma staining for FUS, PDSS2, SMAD4 and HSPA9 was associated with ISUP grade >2 neoplasia, with significance maintained for FUS and SMAD4 in the multivariate analysis. Staining for FUS, PDSS2 and HSPA9 displayed greater risk of biochemical persistence, biochemical recurrence, biochemical failure after prostatectomy and systemic disease, but was not an independent prognostic factor if compared to the classic prognostic factors. Immunoexpression of FUS was the only factor associated with biochemical failure after hormone therapy and salvage radiotherapy. CUL2 and HSPA9 were associated with biochemical failure after radiotherapy in both the univariate and multivariate analysis. No staining for DERL1, YBX1 and pS6 was observed in the study. In conclusion, staining for FUS and HSPA9 in low-grade adenocarcinoma increased the rate of intermediate or high-grade adenocarcinoma, while staining for FUS and SMAD4 in Gleason pattern 4 tissues maintain intermediated risk or high risk. None of the markers showed significance as progress predictors in multivariate analysis. FUS, CUL2 and HSPA9 revealed a potential for the prediction of disease progress following hormone and/or radiotherapy.